PERAN PERANGKAT LUNAK AKUNTANSI PADA KINERJA USAHA KECIL - Wawan Darmawan (AJAR, 2019)
The purpose of this research is to develop a relationship model of accounting software (PLA) to the small businesses performance, i.e. Return on Assets (ROA) and Return on Sales (ROS). The research design is a causal study in Small Businesses located in Makassar. Data is collected through questionnaires that are sent and delivered by the researchers themselves to each respondent totaling 379 Small Businesses. The analysis technique used in this study is simple regression with SPSS software.The findings of this study are that accounting software (PLA) is an important thing in improving the performance of small businesses, because both directly affect financial performance, i.e. Return on Assets (ROA) and Return on Sales (ROS). Recommendations to small businesses in Makassar in order to take technical policies to improve their performance through the use of accounting software (PLA) because they can make their companies more efficient in obtaining profits from their sales and more efficient in using their assets to earn profits.